PERENCANAAN DRAINASE WILAYAH BANYUMANIK SEMARANG - Cut Dede Juanita; Hafidz Noordianto; Pranoto Samto Admojo; Hari Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The flood problem and inundation local often occurring in regions banyumanik, precisely in the intersection of Jalan Durian Raya. A limited drainage channels plus garbage and sedimentation blockage makes the water cannot flow when it rains. This leads to a puddle by the depth of between 10 - 15 cm for 1 - 2 hours. Therefore planning drainage the environmental from can overcome flooding and inundation on jalan durian. In planning, hydrological analysis is performed to seek discharge plan with program HEC-HMS. Acquired discharge flood plan of 39,6 m3/s with repeated periods of 10 years. Then to find out the effectiveness of existing cross section, rivers and drainage channels are modelled with program HEC-RAS. Cross section is planned by condition of steady flow. The result of reckoning using existing programs show a cross section rivers cannot accommodate discharge plan. Similarly with its drainage channels. Treatment done with increased capacity rivers and drainage channels. River cross section in the normalization with three types of cross-section (type I near the lower B = 7 m and H = 3, 5 m, midstream type II B = 6, 5 m and H = 3, 5 m, type III near the upper B = 5 and H = 3, 5 m). While cross section drainages deepened and assembly of a parapet to prevent the overflow.